Antigen specific lymphocyte proliferative response of patients with acute and chronic toxoplasmosis - Khairul Anuar, A.; Rahman, N.; Dighe, V.C.; Nor, Zurainee Mohamed; Suresh, K.; Yano, A. (Faculty of Medicine, University of Malaya, 1999)
In vitro lymphocyte proliferative response of peripheral blood Ieucocytes (PBL) to purified Toxoplasma gondii antigen were evaluated by 3[H] methyl thymidine incorporation in patients acutely and chronically infected with Toxoplasma gondii. PBL from three patients with acute symptomatic toxoplasmosis showed no response to T. gondii antigen during the emergence of anti-Toxoplasma IgM antibodies and the response returned as the infection became chronic. Lymphocytes of twelve chronically infected patients responded positively to the antigen. In all patients the lymphocyte proliferative response to the mitogen, Concanavalin A (Con A) was normal. Analysis of Toxoplasma proliferative response of PBL from a patient with acute toxopiasmosis showed that CD8* cells were responsible for induction of suppression while the response during the chronic infection was mediated by CD4* cells. In human toxoplasmosis there was antigen-specific lymphocyte unresponsiveness during the acute phase of the infection and it appears that the immunesuppression was mediated by CD8+ cells.